A facile approach for 4D microprinting of multi-photoresponsive actuators [data] - Hsu, Li-Yun; Mainik, Philipp; Münchinger, Alexander; Lindenthal, Sebastian; Spratte, Tobias; Welle, Alexander; Zaumseil, Jana; Selhuber-Unkel, Christine; Wegener, Martin; Blasco, Eva (Universität, 2022)
For microscale 4D photoresponsive actuators, light is crucial in two ways. First, the underlying additive manufacturing techniques rely on photopol...